LIFE SCENES OF WOMEN WITH UNPLANNED PREGNANCY AND CONTINUING TO TERM - Kesama, Surassawadee; Naravage, Wanapa; Vittaporn, Supa (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2022)
The objective of this research was to understand the life experiences of women with unplanned pregnancy and continued to term. This qualitative study was conducted using in-depth interviews and non-participant observations of women with unplanned pregnancy and continued to term in two shelters which were Emergency Housing and Home of Grace. The interviews were conducted until the data saturation which took around six months in 17 key informants. The results showed that there were three reasons for unplanned pregnancy which were the family economy, and family and social issues as well as cheating partner. The root cause of pregnancy was caused by the problem of misused contraception, the relationship between couple, and rape. There were 3 scenes in the life of women with unplanned pregnancy. The first scene was life before the pregnancy consists of family matters, economy, and society. The second scene was life during pregnancy include the feeling when women know she’s pregnant, relationships between women and those around them involve irresponsible men and their family rejection. The reason for continued pregnancy was since the pregnancy was over, which made it impossible for an abortion. Also, the cost of an abortion was too expensive, fear of the sin of abortion, and was being persuaded to continue the pregnancy. Lastly, the final scene is after delivery of women who had to select between either giving a child to the temporary rest home or Foundation. The results of the study also voice from women with unplanned pregnancy, showing a feeling of wanting society to understand and not aggravate what happened in their lives. The life experiences of women with unplanned pregnancies can occur before and during pregnancy as well as after delivery. The problems of unplanned pregnancy were the family background, socioeconomic status with expenses burden, irresponsible of men, and different societies with unacceptable of pregnancy before married and pregnancy during study. Finally, this study intends sharing experiences of these women with unplanned pregnancies to make the society aware and understand the lives of women living with unintended pregnancies without blaming that they are promiscuous.